Perlindungan Hukum Atas Kebocoran Data Pribadi Ditinjau dari Undang Undang Nomor 19 Tahun 2019 tentang Informasi dan Transaksi Elektronik dan Implementasinya terhadap Kebocoran Data Pengguna Electronic Healcth Alert Card - Herlan Solehudin; Neni Ruhaeni (Bandung Conference Series: Law Studies, 2022)
Abstract. The government through the Ministry of Health made an eHAC (Electronic Health Alert Card) application and required people traveling outside the city to register for eHAC. Electronic Health Alert Card is an application that functions to verify passengers while traveling. Existing laws and regulations have not been effectively implemented, so there are still many cases of leakage of personal data at the practical level, including the leakage of personal data of users of the EHAC application.Based on the explanation above, this study aims to find out how the implementation of legal protection for leakage from personal users of the electronic health alert card application is reviewed from law number 19 of 2016 concerning Electronic Information and Transactions.This research method uses normative juridical and this research is Descriptive Analysis. Meanwhile, the data used in this study are secondary data obtained from the results of the literature and using the Qualitative Descriptive analysis method.So the result was obtained that the Provisions regarding Personal Data as previously stated were a provision that placed the Electronic System Provider Company as a party that was obliged to always maintain all Personal Data of its consumers. Violations of the provisions of Personal Data have been regulated by Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law). Abstrak. Pada tahun 2021 pemerintah melalui kemenkes membuat aplikasi eHAC (Electronic Health Alert Card) dan mewajibkan masyarakat yang bepergian ke luar kota wajib mendaftar eHAC. Electronic Health Alert Card merupakan aplikasi yang berfungsi untuk melakukan verifikasi penumpang selama bepergian. Aplikasi ini wajib untuk setiap wisatawan dari Negara atau wilayah tertentu yang terkena penyakit, misalnya Covid-19.. Berdasarkan pemaparan diatas, bahwa penelitian ini bertujuan untuk mengetahui bagaimana impelentasi perlindungan hukum atas kebocoran dari pribadi pengguna aplikasi electronic health alert card ditinjau dari undang undang nomor 19 tahun 2016 tentang Informasi dan Transaksi Elektronik. Metode penelitian ini menggunakan yuridis normatif dan penelitian ini bersifat Deskriptif Analisis. Sedangkan data yang digunakan dalam penelitian ini adalah data sekunder yang diperoleh dari hasil kepustakaan dan menggunakan metode analisis Deskriptif Kualitatif. Maka diperoleh hasil bahwa ketentuan-ketentuan mengenai Data Pribadi sebegaimana telah di kemukakan sebelumnya merupakan suatu ketentuan yang menempatkan. Pelanggaran terhadap ketentuan Data Pribadi telah diatur oleh Undang-Undang Nomor 19 tahun 2016 tentang Perubahan Undang-Undang Nomor 11 tahun 2008 tentang Informasi dan Transaksi Elektronik (UU ITE).